Effects of different water management practices on the dry matter production process and characteristics in NERICAs. (3rd April 2019) - Kikuta, Mayumi; Makihara, Daigo; Arita, Naoya; Miyazaki, Akira; Yamamoto, Yoshinori
ABSTRACT: In this study, we aimed to clarify the effects of different water management strategies on dry matter production and yield performance of New Rice for Africa (NERICA) varieties. Dry matter production of NERICA 1 and NERICA 5 was compared with that of Yumenohatamochi, a Japanese upland variety, and Hinohikari, a Japanese lowland variety under three water regimes, i.e. continuously flooded, supplemental irrigation, and non-irrigation (rainfed). Total carbohydrate content in the panicles under different watering regimes was more closely related to post-heading photosynthates than pre-heading reserve assimilates. Dry matter production during ripening tended to decrease under low soil water conditions, whereas the dry matter translocated from the leaf and stem to the panicle tended to increase. Consequently, the distribution ratio of post-heading photosynthates in the total carbohydrate content declined in response to the reduction in available soil moisture. These results indicate that the total carbohydrate content vary depending on the soil water conditions. In NERICAs, dry matter production during ripening was lower than that in Japanese varieties, indicating that their dependence on pre-heading reserve assimilates was greater. In particular, post-heading photosynthate content of NERICA 1 was strongly affected by the variation in water management in comparison with that of other varieties. The decrease in crop growth rate during ripening in NERICA 1 can be mainly attributed to the lower post-heading photosynthate content. Thus, the ability of NERICA 1 to assimilate carbon after heading was considered to be potentially low, which has to be improved to achieve higher yield.